263 Discordant mismatch repair protein expression in synchronous endometrial and ovarian cancers. (13th November 2020) - Kim, S; Tone, A; Pollett, A; Kim, R; Cesari, M; Clarke, B; Eiriksson, L; Hart, T; Holter, S; Lytwyn, A; Maganti, M; Oldfield, L; et al.
Abstract : Objectives: There is no established screening strategy for Lynch syndrome (LS) in synchronous endometrial (EC) and ovarian cancers (OC). Most centers use mismatch repair (MMR) immunohistochemistry (IHC) on endometrium only. We aim to examine the concordance in MMR expression between tumor sites in synchronous EC/OC. Methods: Thirty women with newly diagnosed synchronous EC/OC were prospectively recruited from three cancer centers in Ontario, Canada. Tumor sites were assessed for MMR deficiency by IHC and MSI testing. All women underwent germline testing for MMR mutations. Results: Out of 30 cases, twelve cases (40%) were either MMRd or MSI-H, with 5 (17%) confirmed to have a pathogenic germline mutation: 3 MSH6, 1 MLH1 and 1 PMS2. MMR testing by IHC took place in both ovary and endometrium in 27 cases and results were discordant between two sites in 2 cases (7%). MSI testing in both sites took place in 24 cases, and results were discordant in 2 cases (8%). Out of the 5 cases with confirmed LS, performing IHC alone on endometrium would have missed the diagnosis in 1 case, and performing MSI testing alone on endometrium would have missed the diagnosis in 3 cases, which all had a MSH6 mutation. One case of LS was missed by both IHC and MSI testing. Conclusions: The incidence of LS was high in women with synchronous EC/OC (17%). Given the discordance in IHC and MSI results at the two tumor sites, consideration should be given to direct germline testing in all cases of synchronous EC/OC.